Quality indicators of telemedical care offshore-a scoping review - Michael Hellfritz; Alexander Waschkau; Jost Steinhäuser (BMC, 2021)
Abstract Background Offshore industries operate all around the world in diverse and remote environments. The use of telemedicine to ensure up-to-date medical care for thousands of people offshore has been common practice for decades. Thus, in this setting, extensive experiences with this type of health care delivery have already been gathered, while in other settings this is just beginning. However, the quality of telemedical care on offshore installations is rarely reported yet. The objective of this review was to explore published literature with regards to the following questions: Have any Quality Indicators (QIs) been published for measuring the quality of telemedical care on offshore installations or are there identifiable items that could be used as such QIs? Methods We conducted a comprehensive Scoping Review (PRISMA-ScR) of the published literature using the databases MEDLINE, Cochrane Library, Web of Science (Core Collection), and Google Scholar. Search results were read and QIs or findings from which QIs could be derived were classified according to the dimensions of quality established by Donabedian (structure, process, or outcome QIs). Results The search returned 10,236 non-recurring articles, 45 of which were full-text screened and 15 of which were included in this review. Types of publications were heterogenous. No QIs for the quality of telemedical care offshore have been published yet. Findings that could be the basis for QIs focused on structure quality (11 QIs) followed by process quality (11 QIs), while outcome quality was less common (1 QI). Conclusion Currently, although years of experience with telemedical care on offshore installations exist, there is a paucity of research on a solid data base regarding the quality of telemedical care offshore. The authors derived a list of 24 possible QIs from the findings of the publications for further validation. This could be the basis for implementation and definition of QIs in this and in similar remote settings.